Professor Volodymyr Zemskov — a world-renowned Ukrainian surgeon - Susak, Y.; Zemskov, S.; Dubenko, D. (General Surgery, 2021)
The article describes the professional and scientific way of professor Volodymyr Serhiyovych Zemskov, a prominent Ukrainian surgeon and a founder of the Kyiv Center for Liver, Bile Ducts and Pancreas Surgery which is currently based in the Kyiv City Clinical Hospital No10. The article presents the memories of his students and contemporaries, the facts about his professional biography and career development. The paper describes the main scientific interests of Volodymyr Zemskov, his achievements and scientific work.